Eco²-Screening Method Supporting SME-Product and Process Innovations in Electronics Manufacturing Services Sector - Schusser, Bert; Kolb, Christina; Schusser, Bert; Ehlers, Anika (European Journal of Sustainable Development, 2022)
Consumption exceeds ecological limitations and still the market develops an insufficient incentive for the consideration of environmental aspects in the supply chain. In order to mitigate negative environmental effects, influence is needed in the earliest possible phase of innovation processes. Numerous studies, however, detect systematic use of ecological and economical innovation instruments mainly in large enterprises. In inverse consequence small and medium enterprises (SMEs) implement fewer environmental innovations, even though 99 % of the enterprises in Germany count less than 500 employees and adhere significant innovation potential. In order to provide a scope for action for SMEs an instrument for consideration of environmental product and process implications is needed that claims little economical resources of users and is easily applicable. Based on the Design Science Research Process a Screening method is developed for SMEs in the Electronics Manufacturing Services sector to enable a monitoring of ecological and economical optimization of innovation processes, while not demanding costly Life Cycle Assessment or additional questioning of suppliers. The eco²-screening method uses existing data and follows a modular design.